Troubleshooting of defect formation in injection-moulded thermoplastic tensile specimens by optical microscopy technique - Sirichantra, Jariyavadee (Bulletin of Applied Sciences, 2014)
Voids and blisters often appear in a dumbbell-shaped tensile specimens fabricated by thermoplastic injection molding process. In this study, polypropylene and high density polyethylene were selected to investigate the effects of these defects on tensile properties; i.e., maximum load, tensile strength and elongation at break. From the results of tensile properties for both materials, it was found that the maximum load and tensile strength of specimens without defects were higher than those with defects approximately 2%. As for the elongation at break for both materials, specimens without defects provided final length greater than those with defects significantly (approximately 80%). In addition, the cross-sectional area was observed by an optical microscope, showing that polypropylene specimens contained voids where those of polyethylene had blister defects. This information was then employed to determine the troubleshooting of defect formation in the polymeric specimens fabricated via injection molding